Smokeless Tobacco Use among Madhesi Communities of Nagarain Municipality, Dhanusha, Nepal - Karn, Abhishek; Ghimire, Harishchandra; Khanal, Gayatri; Kandel, Suresh; Sharma, Hari Krishna; Pathak, Susmita (Journal of Health Promotion, 2024)
Smokeless tobacco consumption is a major cause of NCDs and is associated with six leading causes of global death. It is common among people in the Terai area of Nepal with its high burden in the Madhesi community. This study assessed the status of smokeless tobacco (SLT) use and the factors associated with it among the Madhesi community of Nagarain Municipality. A descriptive cross-sectional survey was conducted among 175 people of Nagarain municipality following the systematic random sampling technique. A structured questionnaire was used for data collection using the face-to-face interview technique. The proportion of ever-use and current use of SLT was 70.9% and 70.3% respectively. Males were more likely to consume SLT products (AOR=7.18) than females. Similarly, respondents whose family members (AOR=8.29) and friends (AOR=8.597) used SLT products were more likely to use SLT products themselves. There were 91.9% current users of smokeless-tobacco who reported its use daily. Khaini was the most consumed SLT product followed by betel-quid. The majority of the respondents (70%) had a lower level of knowledge regarding the harmful effects of SLT. The study revealed a significant proportion of smokeless tobacco, linked with the factors like gender, family education, employment status, alcohol consumption, SLT use by family members, and SLT use by friends. To tackle this issue, the strategy can focus on the male, restricting the use of SLT among the family and peer groups.